Bioavailability assessment of some locally manufactured chloroquine phosphate tablets - Baidoo, Samuel Kwaku Peprah (2011)
A thesis submitted to the College of Health Sciences in partial fulfilment of the requirements for Master of Science degree in (Pharmaceutical Analysis and Quality Control),